Sexual Functioning in Young Women and Men: Role of Attachment Orientation. Issue 5 (3rd July 2016) - Dunkley, Cara R.; Dang, Silvain S.; Chang, Sabrina C. H.; Gorzalka, Boris B.
Abstract : Prior research has documented various ways in which adult attachment styles are characteristic of differential behavioral and cognitive patterns within romantic relationships and sexuality. However, few studies have examined the direct influence of anxious or avoidant attachment orientation on sexual function. The aim of the present study was to assess the impact of insecure attachment on sexual function. Undergraduate students completed questionnaires measuring attachment style and sexual functioning. Among women, attachment avoidance tended to be associated with impairments in all aspects of sexual function, whereas anxious attachment tended to be associated with declines in arousal, satisfaction, and ability to achieve orgasm. A different trend was seen in men: Anxious attachment tended to be associated with multiple facets of sexual dysfunction, while avoidant attachment did not correlate with any sexual function deficits and was associated with superior physiological competence. These results suggest that both anxious and avoidant attachment styles are important yet differential predictors of sexual function in men and women.